FAKTOR-FAKTOR YANG MEMPENGARUHI KEPATUHAN PENERAPAN SOP APD PETUGAS LABORATORIUM RS Santa Maria Pekanbaru Tahun 2018 - Ignatius Yulianto Wibowo (Akademi Kesehatan John Paul II Pekanbaru, 2021)
Personal protective equipment (PPE) is the final effort in controlling hazard risks in health laboratories. The use of PPE is carried out by hospitals accompanied by standard operating procedures (SOPs) on how to use them. The compliance of laboratory officers in applying SOPs for the use of PPE is influenced by internal and external factors. The study was conducted to see the compliance of laboratory workers at Santa Maria Hospital Pekanbaru in implementing SOPs for the use of PPE during work. This type of research is descriptive using cross sectional method with a sample of 34 laboratory workers of Santa Maria Hospital Pekanbaru.. The results showed that the working period (p = 0.353), knowledge (p = 0.516) and attitude (p = 0.094) of laboratory workers did not affect the compliance with the use of PPE according to the SOP. On the other hand, understanding of SOPs and supervision of the use of PPE has a significant effect on the compliance of laboratory personnel in using PPE according to SOPs (p = 0.006)